Racism, policy and politics - Murji, Karim, 1960- (Policy Press, 2017)
This book analyses and bridges the gap between critical social research on race and politics by reviewing the academic field of race theorising and scholarship, covering changes in race and racism debates in recent decades, and assessing the extent, scope, and limits of academic engagements with, and impact on, policy and politics.